2023
DOI: 10.3389/fnetp.2023.1124223
|View full text |Cite
|
Sign up to set email alerts
|

Predicting alveolar ventilation heterogeneity in pulmonary fibrosis using a non-uniform polyhedral spring network model

Abstract: Pulmonary Fibrosis (PF) is a deadly disease that has limited treatment options and is caused by excessive deposition and cross-linking of collagen leading to stiffening of the lung parenchyma. The link between lung structure and function in PF remains poorly understood, although its spatially heterogeneous nature has important implications for alveolar ventilation. Computational models of lung parenchyma utilize uniform arrays of space-filling shapes to represent individual alveoli, but have inherent anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This theory has been bolstered in subsequent computational analyses employing, e.g., finite element spring networks ( Wilson and Bachofen, 1982 ; Makiyama et al, 2014 ; Albert et al, 2019 ) or systems of differential equations ( Ma et al, 2023 ) to show that stress accumulates heterogeneously in the lung parenchyma, with the largest stresses found near areas with greater extents of injury. Other spring network simulations have shown that tethering (or stiffening) has both localized and longer length-scale effects on the distribution of lung stress and strain ( Ma et al, 2013 ; Ma et al, 2015 ; Hall et al, 2023 ). Probabilistic methods, based on experimental data, have also been employed to understand the forces contributing to injury propagation, the mechanisms of injury heterogeneity, and the rich-get-richer mechanisms of VILI pathogenesis and offer a complementary perspective to deterministic mechanical models ( Mattson et al, 2022 ; Mattson and Smith, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This theory has been bolstered in subsequent computational analyses employing, e.g., finite element spring networks ( Wilson and Bachofen, 1982 ; Makiyama et al, 2014 ; Albert et al, 2019 ) or systems of differential equations ( Ma et al, 2023 ) to show that stress accumulates heterogeneously in the lung parenchyma, with the largest stresses found near areas with greater extents of injury. Other spring network simulations have shown that tethering (or stiffening) has both localized and longer length-scale effects on the distribution of lung stress and strain ( Ma et al, 2013 ; Ma et al, 2015 ; Hall et al, 2023 ). Probabilistic methods, based on experimental data, have also been employed to understand the forces contributing to injury propagation, the mechanisms of injury heterogeneity, and the rich-get-richer mechanisms of VILI pathogenesis and offer a complementary perspective to deterministic mechanical models ( Mattson et al, 2022 ; Mattson and Smith, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“… Suki et al, 2020 developed a self-healing model on a 2D hexagonal network, however induced fibrosis required a constant perturbation of the agents, rather than fibrosis induced from a single insult. Bates et al, 2007 and Hall et al, 2023 explored fibrosis on 2D hexagonal networks and 3D non-uniform networks, respectively, and both observed clustering and mechanics seen in PF, but neither included rupture, gradient in agent behavior, or self-healing.…”
Section: Discussionmentioning
confidence: 99%
“…We created a non-uniform spring network to represent the parenchymal tissue using a method we have described previously ( Hall et al, 2023 ). Briefly, Poisson Disk Sampling was used to create a semi-organized 2D Voronoi diagram.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations